The unholy cross: Profitability and adoption of climate-smart agriculture practices in Africa south of the Sahara - Nkonya, Ephraim M.; Koo, Jawoo (International Food Policy Research Institute, 2017)
Chapter 8 uses information from several SSA countries to revisit the long-standing problem of practices that demonstrably show both on-farm and off-farm benefits that outweigh investment costs, yet scarcely get adopted. This is clearly a problem that affects CSA as well.